Analisis Pemberitaan Donasi McDonalds Indonesia dalam Perspektif Framing dalam Public Relations - Sari, Asti Novita; Maysiana, Titis; Mahanani, Kanaya Sekar Putri; Oktaviana, Refa (Universitas Pahlawan Tuanku Tambusai, 2025)
This research examines the public relations (pr) strategy used by mcdonald's indonesia in dealing with the boycott issue that circulated on social media and had an impact on the company's reputation. This research uses a framing theory approach to pr to analyse how mcdonald's indonesia shapes narratives and responds to issues that can damage the company's image. data was collected through analysis of mcdonald's official social media posts and several articles. The results showed that McDonald's Indonesia used a framing strategy that included emphasising the company's social responsibility through its community outreach, commitment to product quality and concern for consumers. Although the PR efforts made were quite effective in defusing tensions, some responses to the issue on social media were not entirely positive. This study concludes that the right communication strategy in the event of a reputation crisis is very important to minimise the negative impact on the company's good image in today's digital age.